SOTERIOLOGICAL DIALOGUE BETWEEN WESLEYAN CHRISTIANS AND PURE LAND SECT BUDDHISM - Adamo, David Tuesday (Journal of Dharma, 1989)
Even though Christianity and Buddhism are both universal religions, many significant dialogues have not been embarked upon in the past mainly because of the particularistic and judgmental attitude of many Christians toward all other non-Christian religions, especially Buddhism. As a result, many Christians became either ill-informed or totally ignorant of other religions. However, it is gratifying to note that as Christians all over the world began to have some unavoidable contact with these religions, they started receiving important spiritual challenges that demand serious and mutual understanding of these religions. For this mutual understanding, several dialogues have emerged both at the local and world-wide level.